Kemampuan Guru dalam Pembuatan Soal Higher Order Thinking Skills (HOTS) pada Pembelajaran Tematik Muatan IPA SD Kelas Tinggi - Afifah Akhlaqul Mahmudah; Sukamti Sukamti; M. Anas Thohir; Afifah Akhlaqul Mahmudah; Sukamti Sukamti (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2023)
Abstract: The Industrial Revolution 4.0 has an impact in all aspects including the world of education. Students are required to master various skills, including critical thinking. So, it is necessary to hold regular exercises in order to continue to train students' critical thinking skills. The teacher's role in providing facilities must be supported by adequate abilities, including in preparing HOTS questions to train students' critical thinking skills. This study aims to describe the ability of teachers in making questions, teachers' perceptions ofquestions HOTS, the obstacles encountered, and the solutions applied by teachers to overcome obstacles in the preparation of HOTS questions in thematic learning, especially in science content. The method used is Mix Methods. The results showed that the ability of high-grade teachers in preparing HOTS Science questions was included in the good category. This is indicated by the percentage of the results of the analysis of the suitability of the questions with the guidelines for the preparation of the HOTS questions, showing the percentage is above 50 percent, which means that the teacher's ability in preparing HOTS questions is included in the good category. Abstrak: Revolusi Industri 4.0 berdampak dalam semua aspek termasuk dunia pendidikan. Peserta didik dituntut menguasai berbagai macam keterampilan termasuk critial thinking. Maka, perlu diadakan latihan secara teratur guna terus melatih kemampuan berpikir kritis peserta didik. Peran guru dalam penyediaan fasilitas harus didukung dengan kemampuan yang memadai, termasuk dalam menyusun soal HOTS guna melatih kemampuan berpikir kritis peserta didik. Penelitian ini bertujuan untuk mendeskripsikan kemampuan guru dalam pembuatan soal, persepsi guru tentang soal HOTS, hambatan yang ditemui, dan solusi yang diterapkan oleh guru untuk mengatasi hambatan dalam penyusunan soal HOTS pada pembelajaran tematik khususnya pada muatan IPA. Metode yang digunakan ialah Mix Methods. Hasil penelitian menunjukkan bahwa kemampuan guru kelas tinggi dalam menyusun soal HOTS IPA sudah termasuk dalam kategori baik. Hal ini ditunjukkan dengan persentase hasil analisis kesesuaian soal dengan pedoman penyusunan soal HOTS menunjukkan persentase diatas 50 persen yang artinya kemampuan guru dalam menyusun soal HOTS termasuk dalam kategori baik.